Biosorption of Copper Ions by and Species - Sara Ghaed; Elham Khalilzadeh Shirazi; Reza Marandi (Adsorption Science & Technology)
Biosorption is an innovative method to remove nonbiodegradable pollutants, such as heavy metals, from aqueous solutions using a variety of biomaterials (e.g. bacteria, fungi, algae and industrial and agricultural wastes). Compared with other alternatives, these metabolically inactive and nonliving biomasses of microbial or floral origins are cheaper and more effective in removing metallic elements, some of which are toxic and carcinogenic. The discharge of heavy metals, such as copper ions into wastewater is regarded as a serious threat to the environment. Copper, a widely used metal in different industries, is considered one of the most detrimental elements to aquatic life. In this paper, the following topics are discussed: hazardous effects of copper in wastewater, biological methods of Cu removal (biosorption using bacteria and fungi) and the isotherms and kinetic models of adsorption.